Ventilation in Small-Compartment Fires: The Potential of Fire Retardancy - Al-Waqfi, Mohammed S. El-Ali; Al-Jahmany, Yarub; Al-Jarrah, Jawdat; Rbehat, Diana; Al-Qudah, Omar Ayed (Engineering, Technology & Applied Science Research, 2024)
Modern architecture expands building openings to take advantage of natural light, which may have detrimental effects in case of fire occurrence. The falling panes by the high temperatures may cause fire to spread and endanger lives and property. Based on that and by using Pyrosim software, the current study investigated the effect of natural ventilation on small-compartment fire development and on the latter reaching the flashover phase. The simulated enclosure was a 3.6 m × 3.6 m × 2.9 m room with a closed door of 0.90 m × 2.10 m. The study analyzed the impact of the ventilation opening size and dimensions on fire development and the neutral plane height. The results showed that the ventilation area, rather than its dimensions, was the factor with the most significant impact. Higher ventilation areas reduced the temperatures well below the flashover conditions. The current study reveals the potential of employing natural ventilation to help prevent compartment fires from reaching the flashover stage as well as its consequences on lives and property.